2020
DOI: 10.1111/jace.17486
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh energy storage density and charge‐discharge performance in novel sodium bismuth titanate‐based ceramics

Abstract: Lead-free ferroelectric ceramics are very suitable for electrostatic energy storage capacitors due to their outstanding characteristics of high charge-discharge speed, high power density, and environmental friendliness. Herein, a novel material system as (1−x)Na 0.5 Bi 0.5 TiO 3-xCaZr 0.5 Ti 0.5 O 3 (NBT-CZT, x = 0, 0.05, 0.10, 0.12, 0.15, and 0.20) was designed and prepared for dielectric energy storage ceramics. It demonstrated that the CZT additives induced a phase transition for the NBT ceramics, from ferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 70 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…The process can be simply described as the dielectric capacitor is charged by an external electric field, then the stored electrostatic energy is discharged to a load resistor (13 kΩ in this work), and finally, the voltage or current across the load resistor is collected. 1 The discharged energy density (W d ) can be calculated according to the formula: 1,40…”
Section: Resultsmentioning
confidence: 99%
“…The process can be simply described as the dielectric capacitor is charged by an external electric field, then the stored electrostatic energy is discharged to a load resistor (13 kΩ in this work), and finally, the voltage or current across the load resistor is collected. 1 The discharged energy density (W d ) can be calculated according to the formula: 1,40…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that x = 0.14 sample exhibits excellent responsivity with ξ = 130.69 J/ (kV⋅m 2 ), which is superior to most other reported lead-free ceramics. 4,6,15,19,20,26,27,[45][46][47][48][49] To evaluate the temperature stability of energy storage properties, Figure 10 presents P-E loops of x = 0.14 composition measured in the temperature range of 30°C-180°C under 1 Hz and 10 kV/mm. Figure 10B temperature-dependent W rec and η.…”
Section: Methodsmentioning
confidence: 99%
“…Jiang et al 19 reported that a much enhanced energy storage density of 2.26 J/cm 3 was obtained in 0.8BNT–0.2Ba 0.3 Sr 0.7 TiO 3 ceramics through adding antiferroelectric composition NaNbO 3 (NN). Most recently, a high W rec of 4.77 J/cm 3 at 37.83 kV/mm was achieved in BNT ceramics with substituting low‐loss linear dielectrics CaZr 0.5 Ti 0.5 O 3 20 . Although great progress has been made in achieving high W re value of BNT‐based ceramics, this is almost realized under ultrahigh electric field E ( E > 20 kV/mm).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferroelectric capacitors have rising applications in pulse power applications as energy storage devices due to their extremely short discharge time (microsecond level), such as medical fabrillator, hybrid electric vehicle, etc. [14][15][16][17]. The application of BIT ceramics in ferroelectric capacitive energy storage is noteworthy due to their excellent energy storage performance with high thermal stability and fatigue endurance [18,19].…”
Section: Introductionmentioning
confidence: 99%